Anti-aggressive effects of neuropeptide S independent of anxiolysis in male rats - Beiderbeck, Daniela I.; Lukas, Michael; Neumann, Inga D. (Frontiers in Behavioral Neuroscience, 2014)
Neuropeptide S (NPS) exerts robust anxiolytic and memory enhancing effects, but only in a non-social context. In order to study whether NPS affects aggressive behavior we used Wistar rats bred for low (LAB) and high (HAB) levels of innate anxiety-related behaviour, respectively, which were both described to display increased levels of aggression compared with Wistar rats not selectively bred for anxiety (NAB). Male LAB, HAB and NAB rats were tested for aggressive behavior towards a male intruder rat within their home cage (10 min, resident-intruder [RI] test). Intracerebroventricular (icv) infusion of NPS (1 nmol) significantly reduced inter-male aggression in LAB rats, and tended to reduce aggression in HAB and NAB males. However, local infusion of NPS (0.2 or 0.1 nmol NPS) into either the nucleus accumbens or the lateral hypothalamus did not influence aggressive behavior. Social investigation in the RI test and general social motivation assessed in the social preference paradigm were not altered by icv NPS. The anti-aggressive effect of NPS is most likely not causally linked to its anxiolytic properties, as intraperitoneal administration of the anxiogenic drug pentylenetetrazole decreased aggression in LAB rats whereas the anxiolytic drug diazepam did not affect aggression of HAB rats. Thus, although NPS has so far only been shown to exert effects on non-social behaviors, our results are the first demonstration of anti-aggressive effects of NPS in male rats.